IWII Wound Infection in Clinical Practice consensus document: 2022 update. (1st December 2022) - Swanson, Terry; Ousey, Karen; Haesler, Emily; Bjarnsholt, Thomas; Carville, Keryln; Idensohn, Patricia; Kalan, Lindsay; Keast, David H; Larsen, Donna; Percival, Steven; Schultz, Gregory; Sussman, Geoff; et al.
Abstract : Abstract: Wound infection is a major challenge for clinicians globally, with accurate and timely identification of wound infection being critical to achieving clinical and cost-effective management, and promotion of healing. This paper presents an overview of the development of the International Wound Infection Institute (IWII)'s 2022 Wound Infection in Clinical Practice consensus document. The updated document summarises current evidence and provides multidisciplinary healthcare providers with effective guidance and support on terminology, paradigms related to biofilm, identification of wound infection, wound cleansing, debridement and antimicrobial stewardship. Integral to the update is revision of wound infection management strategies which are incorporated within the IWII's Wound Infection Continuum (IWII–WIC) and management plan. The aim of the 2022 IWII consensus document update was to provide an accessible and useful clinical resource in at least six languages, incorporating the latest evidence and current best practice for wound infection and prevention. Dissemination techniques for the consensus are discussed and highlighted.